Analisis Faktor Penentu Terjadinya Persistensi Laba pada Perusahaan Manufaktur di BEI - Desy Mariani; Suryani Suryani (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study aims to analyze the factors that determine Earning Persistence. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The sampling method used in this study is a purposive sampling method where according to the established criteria, 53 companies are obtained and the data used is secondary data. The analytical technique used in this study is multiple linear regression analysis using the Statistical Product and Service Solutions (SPSS) v.20.0 program. The results showed that Audit Fee and Cash Flow Volatility had a positive and significant effect on Earnings Persistence, Sales Volatility had a negative and significant effect on Earnings Persistence, Debt Level and Operating Cycle had no effect on Earning Persistence.